Toxic encephalopathy and peripheral neuropathy of poisoning by Avermectin Pyridine: a case report and a review of the literature - Diao, Jiuzhou; Zhou, Qingbo (Frontiers in Neurology, 2023)
Background Avermectin Pyridaben (AVP) is an insecticide with extreme neurotoxicity in human, causing critical symptoms such as nausea, vomiting, coma and respiratory failure within a short time after oral ingestion. Neurological sequelae or even death may occur because of delayed treatment or excessive toxic dose. Case presentation We report a 15-year-old girl who presented with coma, respiratory failure, limb weakness, ataxia symptoms after ingestion of a toxic dose of AVP. Soon after the poisoning, the patient was treated with life-saving mechanical ventilation and haemodialysis. Subsequently brain Magnetic Resonance Imaging (MRI) and nerve conduction study (NCS) and electromyography (EMG) demonstrated toxic encephalopathy and peripheral nerve injury. Over the next 2 months the patient’s limb function gradually recovered under treatment with hyperbaric oxygen, glucocorticoid pulses and neurotrophic drugs. Conclusion This case documents a rare presentation of toxic encephalopathy complicated with peripheral neuropathy following AVP poisoning. Seven other similar cases of poisoning in terms of common symptoms and effective treatment have also been summarised for providing clinicians with experience in diagnosis and therapy.